Frequência de Eventos Extremos de Precipitação para Pelotas/RS - Silva, Morgana Vaz da; Cardoso Neta, Luciana (Ciência e Natura, 2013)
The aim this study was to determine and verify whether there were trends in the number of precipitation events greater than 20 mm and 70 to Pelotas/RS, for the period 1966-2012. To check whether there were any trends in the number of precipitation events we used the Mann-Kendall. From the results obtained it was concluded that in February we observed the largest number of rain events greater than 20 mm and 2002 were the most frequently precipitation above 70 mm. According to the Mann-kendall trend wasn’t observed in the number of extreme precipitation events for the period under analysis.